1982
DOI: 10.1021/np50024a012
|View full text |Cite
|
Sign up to set email alerts
|

Furoquinoline Alkaloids of Teclea ouabanguiensis

Abstract: From the stem bark of Teclea ouabanguiensis Aubrev. & Perr. (Rutaceae), six furoquinoline alkaloids have been isolated and characterized. Previously known alkaloids, but new to this plant, were tecleaverdoomine (1), tecleine (3), flindersiamine (4), montrifoline (nkolbisine) ( 5) and kokusaginine (6), while tecleamine 2 is reported from a natural source for the first time. Spectroscopic and chemidal evidence is presented for the structure of the new isolate 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 9 publications
(23 reference statements)
0
30
0
Order By: Relevance
“…Not withstanding that these alkaloids are typical of the genus Zanthoxylurn as a whole, they concluded that Z. tessrnannii (as F. tessmannii) is conspecific with Z. gilletii. As part of our investigations on Cameroonian Rutaceae of medicinal interest (7,8,9) and in the hope of clarifying the taxonomic position of Z. tessrnannii, we investigated in detail the alkaloidal as well as the neutral components of the root bark of Z. tessmannii from three localities. We report herein the results of our study.…”
Section: Introductionmentioning
confidence: 99%
“…Not withstanding that these alkaloids are typical of the genus Zanthoxylurn as a whole, they concluded that Z. tessrnannii (as F. tessmannii) is conspecific with Z. gilletii. As part of our investigations on Cameroonian Rutaceae of medicinal interest (7,8,9) and in the hope of clarifying the taxonomic position of Z. tessrnannii, we investigated in detail the alkaloidal as well as the neutral components of the root bark of Z. tessmannii from three localities. We report herein the results of our study.…”
Section: Introductionmentioning
confidence: 99%
“…A sample of AR5 was then supplied by Dr. Al-Rehaily and investigated by MS and NMR spectroscopy. These data indicated that it was in fact nkolbisine (13) (Ayafor et al, 1982).…”
Section: Resultsmentioning
confidence: 87%
“…1). These six compounds were identifi ed as kokusaginine (1) (Al-Rehaily et al, 2003), tecleaverdoornine (2) (Ayafor et al, 1982), maculine (3) (Yenesew and Dagne, 1988) and montrifoline (4) (Wondimu et al, 1988) together with lupeol (Hafez et al, 1988) and β-sitosterol glucopyranoside (6) (Seo et al, 1978) by comparison of 1D and 2D NMR data with reported data.…”
Section: Resultsmentioning
confidence: 99%